Do Females with Bulimia Nervosa and Eating Disorder Not Otherwise Specified Have Selective Memory Biases?. Issue 5 (September 2015) - Griffith, Emma; Kuyken, Willem; Watkins, Ed; Jones, Alysun
<x content-type="archive" xml:space="preserve">Abstract</x> Background: The cognitive model suggests memory biases for weight/shape and food related information could be important in the maintenance of eating disorders. Aims: The current study aims to evaluate this and extend previous research by (a) including females with eating disorder not otherwise specified (EDNOS) as a discreet group; (b) considering whether levels of hunger and the pleasantness of the stimulus words are important in word recall. Method: The study includes three groups of females, 16 with bulimia nervosa, 18 with EDNOS and 17 non-dieting general population controls. All participants completed a self-referential encoding and memory recall task. Results: A main effect of word type (p < .01) with no group by word type interaction or between group difference was found. A priori contrasts indicated that both eating disorder groups recalled significantly more weight/shape and food words compared to all other word categories (p < .01) compared to the control group; with no significant difference found between the eating disorder groups. In relation to the recall of food words, no significant differences were found between groups for levels of hunger. Both eating disorder groups rated the negative weight/shape (p < .01), negative food (p < .01) and neutral body words (p < .01) as more unpleasant than the control group. Conclusions: The implications for cognitive theory and future research are discussed.